Increases in mean annual temperature do not alter soil bacterial community structure in tropical montane wet forests. Issue 4 (29th April 2016) - Selmants, Paul C.; Adair, Karen L.; Litton, Creighton M.; Giardina, Christian P.; Schwartz, Egbert
Abstract: Soil bacteria play a key role in regulating terrestrial biogeochemical cycling and greenhouse gas fluxes across the soil‐atmosphere continuum. Despite their importance to ecosystem functioning, we lack a general understanding of how bacterial communities respond to climate change, especially in relatively understudied ecosystems like tropical montane wet forests. We used a well‐studied and highly constrained 5.2°C mean annual temperature (MAT) gradient in tropical montane wet forests on the Island of Hawaii to test the hypothesis that long‐term, whole‐ecosystem warming and the accompanying increase in belowground carbon flux increase the diversity and alter the composition of soil bacterial communities. Across this MAT gradient, dominant vegetation, substrate type and age, soil moisture, and disturbance history are constant, allowing us to effectively isolate the influence of rising MAT on soil bacterial community structure. Contrary to our hypothesis, we found that the richness, evenness, and phylogenetic diversity of the soil bacterial community remained remarkably stable with MAT and that MAT did not predict variation in bacterial community composition despite a substantial increase in belowground soil carbon fluxes across the gradient. Our results suggest that other factors that are constant across this gradient—such as soil pH, water availability and plant species composition—may be more important than warming in influencing soil bacterial community composition and diversity, at least within the temperature range studied here ( 13–18°C MAT). Ours is the first study to demonstrate stability of soil bacterial community structure with rising MAT and increased belowground carbon flux in a tropical wet forest ecosystem. Moreover, our results add to growing evidence that the diversity and composition of soil bacterial communities dominated by Proteobacteria and Acidobacteria in low‐pH forest soils may be insensitive to the direct effect of climate warming.